2019
DOI: 10.1155/2019/7901760
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of an Assessment Tool for the Screening of Neurotoxic Effects in Agricultural Workers in Chile

Abstract: There is a substantial use of pesticides within the agricultural industry of Chile, with neurotoxic effects through mechanisms of acetylcholinesterase inhibition. These pesticides result in deterioration in health, increasing the risk of diseases such as Parkinson's and Alzheimer's in highly exposed occupational population. To date, there are no brief assessment tools to monitor cognitive impairment in agricultural workers chronically exposed to these pesticides. Method. 234 agricultural workers and 305 nonagr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The patients with bvFTD were referred from two public hospitals in Santiago, Chile: Complejo Asistencial Barros Luco and Hospital El Salvador. The clinical diagnosis was performed by two cognitive neurologists according to the current criteria for bvFTD ( 30 ). The healthy control subjects were recruited by dissemination through the University buildings and social media.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients with bvFTD were referred from two public hospitals in Santiago, Chile: Complejo Asistencial Barros Luco and Hospital El Salvador. The clinical diagnosis was performed by two cognitive neurologists according to the current criteria for bvFTD ( 30 ). The healthy control subjects were recruited by dissemination through the University buildings and social media.…”
Section: Methodsmentioning
confidence: 99%
“…Each item is scored from 0 to 3 points, where a higher score represents better performance. This test shows suitable psychometric properties in the Chilean population ( 30 ). Second, we used the FAS and animal version of the Controlled Oral Word Association Test [COWAT; ( 35 )] to assess cognitive flexibility.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously published our findings regarding the reliability and validity of a questionnaire used to assess OP pesticide exposure to adult agricultural workers in Maule, Chile ( Muñoz-Quezada et al, 2019a ). Moreover, we also previously published a manuscript of another research that aimed to validate a short battery for the early detection of cognitive impairment in agricultural workers ( Lucero et al, 2019 ). The main difference between this study and the previous ones is that it corresponds to a questionnaire validated with rural schoolchildren and not with agricultural workers.…”
Section: Methodsmentioning
confidence: 99%
“…The general validity test is called valid if the corrected item-total correlation value is greater than 0.30 then it can be concluded that the value is valid. If you look at the data, Table 1 shows that all variable indicators have a corrected item-total correlation value above 0.30 so that it is declared valid, as in the study (Lucero et. al., 2019) the level of instrument validity is good if the validity value is above 0.30.…”
Section: Validity and Reliabilitymentioning
confidence: 96%